2022
DOI: 10.3390/microorganisms10020275
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bioorganic Fertilizer on Panax notoginseng Improves Plant Growth by Altering the Rhizosphere Microbiome Structure and Metabolism

Abstract: Bioorganic fertilizers can alleviate (a) biotic stresses and sustainably increase crop yields. The effect of bioorganic fertilizers on the rhizosphere bacterial community of Panax notoginseng and soil metabolism remains unknown. Here, we tracked the changes in the soil physicochemical properties, bacterial microbiota responses, and soil metabolic functions after the addition of a bioorganic fertilizer in a P. notoginseng field. The application of a bioorganic fertilizer reduced the soil acidification, improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Only a small percentage of the bacterial species in the soil samples came from the organic manure itself. Shi [ 72 ] found that Shannon diversity decreased, and bacterial community composition shifted in the bioorganic fertilizer treatment compared to non-fertilizer treatment. There was no significant difference in species richness between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small percentage of the bacterial species in the soil samples came from the organic manure itself. Shi [ 72 ] found that Shannon diversity decreased, and bacterial community composition shifted in the bioorganic fertilizer treatment compared to non-fertilizer treatment. There was no significant difference in species richness between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the numerous advantages of biofertilizers, extensive research has been conducted in this eld. For instance, bioorganic fertilizers have been successfully used in various crops such as peas and oats (Jannoura et al 2014), Panax notoginseng (Shi et al 2022), grapes , apples (Gu et al 2024), and walnuts (Du et al 2022) due to their high e ciency, fast results, and cost-effectiveness. Microbial fertilizers, which contain a plethora of bene cial microorganisms, are primarily employed for biological control of plant and soil diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable fertilizer plan is needed to ensure the long-term growth of agriculture [21]. To improve soil health and increase crop yields, organic fertilizers are a great alternative to chemical fertilizers [22,23]. The benefits of applying organic fertilizer to soil include the strengthening of soil physical properties, the preservation of fertilizer and water functions, the enhancement of soil nutrient content, the improvement of soil microbial community structure and microenvironment, and the promotion of crop growth for roots and branches [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%